2015
DOI: 10.1177/155892501501000318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Finishing Process on Comfort Characteristics of Stretchable Cotton Fabric

Abstract: The comfort characteristics of fabrics (especially thermal insulation and permeability properties) are closely associated with the changes in their structural parameters. The reaction of a stretchable fabric, either after the finishing process or after a mechanical deformation, is higher than the reaction of conventional fabrics. The reaction after the finishing process is usually expressed in terms of density, thickness or mass increase, and in dimensional changes. The structural changes influence thermal ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This results in a change and in most cases increase in thread density. This increment in number of yarns in unit length of fabric is reported more prominent in case of fabrics with elastane [4], [12]. As far as the effect of spandex content in weft yarn is concerned, the warp density increases with spandex amount in weft yarn.…”
Section: Effect Of Spandex Content On Thread Countmentioning
confidence: 99%
“…This results in a change and in most cases increase in thread density. This increment in number of yarns in unit length of fabric is reported more prominent in case of fabrics with elastane [4], [12]. As far as the effect of spandex content in weft yarn is concerned, the warp density increases with spandex amount in weft yarn.…”
Section: Effect Of Spandex Content On Thread Countmentioning
confidence: 99%
“…Fabrics containing spandex are dimensionally unstable compared to the conventional fabrics. [2][3][4] This poor dimensional stability and its optimization is a real challenge for the stretch fabric manufacturers. Therefore, these fabrics are subjected to heat setting treatment to get a satisfactory dimensional stability.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted on the air permeability, water vapor permeability and wicking properties of fabrics. Gorjanc and Bizjak [4] investigated the impact of the pre-finishing process (scouring/bleaching) on the comfort characteristics of pure cotton fabrics and of cotton fabrics with elastane in the weft direction in plain and twill weave. The results indicated that water vapor resistance decreased following pre-finishing of the fabrics.…”
Section: Introductionmentioning
confidence: 99%